2005
DOI: 10.1021/bi0521801
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Calmodulin Bound to a Calcineurin Peptide:  A New Way of Making an Old Binding Mode,

Abstract: Calcineurin is a calmodulin-binding protein in brain and the only serine/threonine protein phosphatase under the control of Ca2+/calmodulin (CaM), which plays a critical role in coupling Ca2+ signals to cellular responses. CaM up-regulates the phosphatase activity of calcineurin by binding to the CaM-binding domain (CBD) of calcineurin subunit A. Here, we report crystal structural studies of CaM bound to a CBD peptide. The chimeric protein containing CaM and the CBD peptide forms an intimate homodimer, in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 38 publications
6
87
1
Order By: Relevance
“…The model was further extended to include calmodulin binding to its targets. It was shown that autoinhibitor domains of CaMKII and PP2B bound to the same, open, conformation of calmodulin (22,23). Therefore, we introduced the binding of both CaMKII and PP2B to calmodulin in the R state, independent of the number of bound calcium ions.…”
mentioning
confidence: 99%
“…The model was further extended to include calmodulin binding to its targets. It was shown that autoinhibitor domains of CaMKII and PP2B bound to the same, open, conformation of calmodulin (22,23). Therefore, we introduced the binding of both CaMKII and PP2B to calmodulin in the R state, independent of the number of bound calcium ions.…”
mentioning
confidence: 99%
“…In the course of our work we also noted that these fusion proteins seem to prevent aggregation, and that they provided more stable NMR samples than the regular noncovalent Ca 2ϩ -CaM CaMBD-peptide complexes. Previously, Jia and coworkers (45) have determined a crystal structure for Ca 2ϩ -CaM fused with the CaMBD of calcineurin via a poly-Gly linker and they uncovered a unique complex, in which CaM forms a ''head to tail'' dimer through the two bound CaMBDs. More recently, the same group has demonstrated that the crystal structures of their CaM fusion protein and that of the complex with a noncovalently bound CaMBD peptide were essentially identical (C␣ r.m.s.d.…”
Section: Discussionmentioning
confidence: 99%
“…pET-21a empty vector (EV) was bought from Novagen (Madison, WI). pET21a-CaM was constructed by our own faculty (18). pcDNA3-HA-TRAF3 was generous gift from Micheal Karin (University of California San Diego, La Jolla, CA) (19).…”
Section: Construction Of Plasmids and Reagentsmentioning
confidence: 99%
“…pcDNA3-HA-TRAF3 was used as the template and the following primers were used to obtain slice variant as indicated: for pcDNA3-TRAF3-C (T3C, aa 314-543) construction forward primer, 5 0 -ACTGAATTCCCCTTCCGGCAGAACTG-3 0 ; reverse primer, 5 0 -CTCGAGTCAGGGATCGGGCAGATCCGA-3 0 ; for pcDNA3-TRAF3-N (T3N, aa 1-313) construction forward primer 5 0 -GTGGTGGAATTCATGGAGTCGA-3 0 ; reverse primer 5 0 -GAC TCGAGTCACCGGATCTCC-3 0 . Previously, we have reported a two-round PCR procedure for construction of CaM fusion protein (18). The same PCR strategy was adopted for construction of pET21a-CaM-TRAF3-C, which contains a continuous DNA sequence coding for CaM, a thrombin cleavage site, the TRAF domain of TRAF3 (TRAF3 amino acids: 314-543) and a 63His tag.…”
Section: Construction Of Plasmids and Reagentsmentioning
confidence: 99%